2004
DOI: 10.1385/mo:21:1:21
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin Is a Dual Inhibitor of Farnesyltransferase and Geranylgeranyltransferase I with Antitumor Activity Against Breast Cancer In Vivo

Abstract: Gliotoxin is a natural mycotoxin with immunosuppressive and antimicrobial activity. Inhibition of farnesyltransferase (IC50 80 microM) and geranylgeranyltransferase I (IC50 17 microM) stimulated interest in the potential antitumor activity of this epidithiodioxopiperazine. Gliotoxin inhibited proliferation of six breast cancer cell lines in culture with mean +/- SD IC50 289 +/- 328 microM (range 38-985 microM); intracellular farnesylation of Lamin B and geranylgeranylation of Rap1A were inhibited in a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 45 publications
5
79
0
Order By: Relevance
“…Inhibition of HDACs may contribute to the induction of cell cycle arrest during the G 1 and/or G 2 phase, differentiation, and/or apoptosis in various cancer cells (Marks et al, 2001). Several HDAC inhibitors can halt tumor growth in animal models with little toxicity, while the inhibition of HDAC is normally not sufficient to cause cell death in nontumor cells (Vigushin et al, 2001;Atadja et al, 2004). This selectivity for tumor cells makes these compounds particularly attractive for cancer therapy, and several newly developed HDAC inhibitors have been tested on cancer patients in clinical trials (Piekarz and Bates, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HDACs may contribute to the induction of cell cycle arrest during the G 1 and/or G 2 phase, differentiation, and/or apoptosis in various cancer cells (Marks et al, 2001). Several HDAC inhibitors can halt tumor growth in animal models with little toxicity, while the inhibition of HDAC is normally not sufficient to cause cell death in nontumor cells (Vigushin et al, 2001;Atadja et al, 2004). This selectivity for tumor cells makes these compounds particularly attractive for cancer therapy, and several newly developed HDAC inhibitors have been tested on cancer patients in clinical trials (Piekarz and Bates, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(where d1 and d2 are the two perpendicular diameters) [14]. Using another set of the inoculated 20 mice, tumors were resected at day 20 after subcutaneous inoculation of SYO-1 cells, and tumor weight was measured after the invaded internal organs were removed from them as well as possible.…”
Section: Transfectionmentioning
confidence: 99%
“…HDI induce growth arrest, differentiation, and/or apoptosis in a variety of transformed cell lines and inhibit tumor development in rodents (Cohen et al, 1999;Margueron et al, 2004). Several studies in animal models have reported the efficacy of some of these inhibitors in blocking tumor growth (Marks et al, 2000), mammary tumors in particular (Vigushin et al, 2001). Phase I and II clinical trials are currently under way for several of these molecules (Kramer et al, 2001) to test whether HDI might provide an alternative therapeutic approach for the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%